Strategy of the Principal in Improving Teacher’s Work Motivation - Kurniati, Neneng; Kristiawan, Muhammad; Wardiah, Dessy (Yayasan Sembilan Pemuda Indonesia, 2023)
This study aims to describe and analyze the principal’s strategy in increasing teacher motivation. at State Senior High School 4 Ogan Komering Ulu, jl. Cabbage. Wahab Sarobu Air Paoh Baturaja Ogan Komering Ulu. This research use desciptive qualitative approach. This research was conducted at State Senior High School 4 Ogan Komering Ulu, jl. Cabbage. Wahab Sarobu Air Paoh Baturaja Ogan Komering Ulu with the subject of this research is the teacher. Data collection techniques using observation, interviews and documentation. The results of the study are the steps of the principal’s leadership strategy in increasing teacher work motivation at SMA Negeri 4 OKU by giving appreciation or appreciation to teachers who have worked well, providing training and self-development to teachers to improve their quality, providing an environment which is comfortable for all school members to work well, gives freedom to teachers to work more creatively in teaching, besides that the principal determines the targets that must be achieved. By making a clear work program, teachers will feel directed and motivated to work better.